Numerical methods for solving fuzzy nonlinear equations - Amirah Ramli (Terengganu: Universiti Malaysia Terengganu, 2012)
Nowadays, nonlinear equations play a major role such as in engineering problem, science problem and more. Repeatedly, more and more researchers come out with new numerical methods for solving nonlinear problems. However, in real world problems not all the parameters are presented by crisp number but also are presented in fuzzy number.